The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.5603/cj.a2015.0015
|View full text |Cite
|
Sign up to set email alerts
|

White blood cell count to mean platelet volume ratio as a novel non-invasive marker predicting long-term outcomes in patients with non-ST elevation acute coronary syndrome

Abstract: (p < 0.001). In an adjusted cox regression model, the elevated WMR was independently predicted the incidence of MACE (hazard ratio 2.419, p < 0.001). Conclusions:The elevated baseline WMR independently predicted the MACE incidence in patients with NSTE-ACS during long-term follow-up. (Cardiol J 2015; 22, 4: 437-445) Key words: white blood cell to mean platelet volume ratio, non-ST elevation acute coronary syndrome, major adverse cardiovascular events

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
38
3
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 32 publications
5
38
3
4
Order By: Relevance
“…Increased WBCs may appear as a significant factor showing impaired microvascular reperfusion. Recently, Dehghani et al [11] investigated a novel parameter called WMR as a marker predicting long-term outcomes in patients with NSTEMI. They suggested that WMR is a better predictor of worse outcomes in patients with NSTEMI than WBC and MPV [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased WBCs may appear as a significant factor showing impaired microvascular reperfusion. Recently, Dehghani et al [11] investigated a novel parameter called WMR as a marker predicting long-term outcomes in patients with NSTEMI. They suggested that WMR is a better predictor of worse outcomes in patients with NSTEMI than WBC and MPV [11].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Dehghani et al [11] investigated a novel parameter called WMR as a marker predicting long-term outcomes in patients with NSTEMI. They suggested that WMR is a better predictor of worse outcomes in patients with NSTEMI than WBC and MPV [11]. In light of these evidences, we decided to evaluate the prognostic value of WMR with a large number of patients with STEMI undergoing pPCI and demonstrated that WMR is a better indicator of predicting the poor outcomes in STEMI than MPV, RDW, PLR-NLR and WBC-MPV combinations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have read the article entitled "White blood cell count to mean platelet volume ratio as a novel non-invasive marker predicting long-term outcomes in patients with non-ST elevation acute coronary syndrome" [1] with great interest. Both leukocytes and platelets have been reported to be involved in several cardiovascular (CV) diseases through inflammatory pathways.…”
mentioning
confidence: 99%
“…The close relationship between inflammation, aggregation, and atherosclerosis progression has become a field of intensive research. The study by Dehghani et al [1] evaluated the predictive role of white blood cell count/mean platelet volume (WBC/MPV) ratio (WMR) in long-term outcomes of acute coronary syndrome (ACS) patients. However, we have some comments regarding the presented study.…”
mentioning
confidence: 99%